1991
DOI: 10.1111/j.1365-2826.1991.tb00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Gonadotropin‐Releasing Hormone Secretion: Methodological Aspects of in vitro Systems

Abstract: The regulation of gonadotropin-releasing hormone (GnRH) secretion from the medial basal hypothalamus (MBH) of adult male rats has been studied using two types of in vitro methods, the dynamic superfusion and static incubation systems. We compared both systems for methodological features including stability of baseline GnRH release and technical limitations or artefacts as well as for response to norepinephrine and naloxone, an opiate antagonist, which represent the two major physiological neuromodulators regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
5
1
Order By: Relevance
“…First, Azad incu bated a hypothalamus divided in six pieces by 1 longitu dinal and 2 transversal cuts, this might have helped the penetration of the immunoglobulins within the tissue; and, second, they incubated their tissues in a metabolic shaker. Mechanical agitation has been reported to in crease basal GnRH output [13]. indeed, they reported basal values more than 20-fold higher than those reported in the present study.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…First, Azad incu bated a hypothalamus divided in six pieces by 1 longitu dinal and 2 transversal cuts, this might have helped the penetration of the immunoglobulins within the tissue; and, second, they incubated their tissues in a metabolic shaker. Mechanical agitation has been reported to in crease basal GnRH output [13]. indeed, they reported basal values more than 20-fold higher than those reported in the present study.…”
Section: Discussioncontrasting
confidence: 67%
“…This system was selected because it has been reported to have some advantages over a perfusion system [ 13]. Moreover, based on the observation that PRL exerts a more pro nounced suppressive effect on plasma gonadotropin lev els in female than in male rats [6. 14], we also examined whether the addition of testosterone (T), dihydrotestos terone (DHT).…”
Section: Introductionmentioning
confidence: 99%
“…GnRH secretion from MBH was studied for 6 h using an in vitro system as described and validated in detail elsewhere [12]. Briefly, the static incubation system consisted o f a single MBH seated in a 5-ml glass scintillation vial and bathed in 1 ml of incubation medium con sisting of Earle's balanced salt solutions (pH 7.4) with added 5 mM HF.PES (Hoechst) and 0.25% gelatin was gassed continuously with 95% 0 '/5% COj.…”
Section: Hypothalamic Incubation Systemsmentioning
confidence: 99%
“…Thus, several in vivo (Levine and Ramirez, 1986, in the rat; Caraty and Locatelli, 1988, in the ram) and in vitro (review in Wibullaksanakul and Handelsman, 1991) techniques have been developed. The in vitro approach has the advantage of allowing the direct testing of the effect of various substances on the secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of in vitro methods have been described: superfusion (Gallardo and Ramirez, 1977, in the rat; Knight, 1983, in the chicken) and static incubation (Rotsztejn et al, 1976, in the rat; Katz et al, 1990, in the chicken). Wibullaksanakul and Handelsman (1991) compared both systems in a systematic study and concluded the superiority of static incubation, which they judge technically simpler, more robust and accurate than superfusion. With the aim of studying the regulation of LHRH secretion in the chicken, we have developed an incubation system for chicken mediobasal hypothalamus (MBH) and a radioimmunoassay sensitive enough for reliable measurement of the amounts of chicken LHRH-I released in vitro.…”
Section: Introductionmentioning
confidence: 99%